KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS ENOK TEMBILAHAN KABUPATEN INDRAGIRI HILIR - jurnalmap map; Eskalinda ÔÇÄ (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This study aims to describe the quality of health services in Enok Tembilahan Health Center. This research is a type of quantitative descriptive research, with dimensions of service quality according to Parasuraman, Zeithaml and Berry consisting of Tangibles (direct evidence), Reliability, Responsiveness (responsiveness), Assurance (assurance) and Empathy. The results of studies that have been conducted on service quality at Enok Tembilahan Health Center in health services, from the five dimensions namely Tangibles (direct evidence), Reliability, Responsiveness, Assurance and Empathy, the quality of service is good. Keywords: service quality, reliability, responsiveness, assurance, empathy